The Attendance of Independent Candidates in Local Head Election as a Effort to Improvement The Government System - Joko Martono; Budimansyah Budimansyah; Annurdi Annurdi (Faculty of Law, Universitas Pekalongan, 2017)
The nature of political party is accentuated their interest that causes the decrease of public confidence in the political party. It affects the election of local heads when the candidate supported by the political party in the election process. So that the presence of regulation that opens the opportunity for independent candidates in the election of local head, raises the hope to improve the government system. This research type is normative juridical research, and the data used for this research are some legislation, documents, and books relating the election of local head. The result of this research revealed that independent candidates that elected as local head face problems when they must be able to maintain a balance with the local parliament as a consequence of did not get support from political parties.Keywords: Independent Candidate, Local Head Election